Crisis of the Economic and Social Model of the Nordic Countries: The Experience of Denmark, Norway, Finland and Sweden - Ekaterina A. Demina (Регионология, 2020)
Introduction. The Nordic countries are the most economically developed and stable ones in terms of the political and social context. However, the processes of globalization, social and demographic change, business development, increased competition and commercial interests modify the functioning of the economic and social model of the Nordic countries, which experienced a number of crisis phenomena at various stages of its development. The objective of this piece of research is to analyze the prospects for the development of the Nordic model of the social state based on the study of its structure and historical development.